DETERMINANTS OF FARMER’S PERCEPTION OF PROSTEPHANUS TRUNCATUS (HORN) DAMAGES AND LOSSES ON STORED MAIZE IN TOGO AND BENIN (WEST AFRICA) - Kokou Edoh Adabe; Abbevi Georges Abbey; Yendouban Lamboni; Koffi Moise Djade; Agbéko Kodjo Tounou; Kerstin Hell (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
Prostephanus truncatus is one of the most damaging post-harvest pests of stored maize in Africa. Research Institutions disseminated Various control strategies during the 1990s in West Africa with significant results. What is farmers’ perception of this pest in decades after those control strategies? This study aimed to assess determinants of farmers’ perception of current damages and losses caused by Prostephanus truncatus on stored maize in southern of the two countries (Benin and Togo). 300 maize farmers (150 from Togo and 150 from Benin) were randomly selected from 10 villages per country. Descriptive statistics were used in addition to Logit and Tobit regression analysis. The results showed that 38% of farmers (35% in Togo and 41% in Benin) still perceive Prostephanus truncatus as the most damaging pest of stored maize. Logit's results showed that factors influencing farmers’ perception of Prostephanus truncatus were group membership, contact with extension agents, and period of maize harvesting. The results from the Tobit regression model showed that factors such as the maize variety, the form of maize storage (with husk), and the storage period influence the extent of damage and loss caused by Prostephanus truncatus. Farmers still perceive Prostephanus truncatus as the main post-harvest pest causing high damage and losses on maize. It is recommended that further dissemination of maize storage technology to reduce postharvest losses.